The Effect of Financial Performance on Company Value with Corporate Social Responsibility as a Moderating Variable in Food and Beverage Companies Listed on the Indonesia Stock Exchange 2021-2023 - Alfira rezky Amalia; Muhammad Nasrun; Syamsuddin Syamsuddin (International Journal of Economic Research and Financial Accounting, 2025)
This study aims to determine the effect of financial performance on company value using Corporate Social Responsibility as a moderating variable focused on food and beverage companies listed on the Indonesia Stock Exchange for the period 2021-2023. This study uses a quantitative method, the sample in this study was taken from the Indonesia Stock Exchange (IDX) with a total of 15 Food and Beverage Sector Companies. The research data was obtained using secondary data. The results of the study from the data processed using SPSS 26 statistical calculations. Based on the partial output of SPSS 26, the results of the study indicate that financial performance has a positive and significant effect on company value. Corporate social responsibility is able to positively moderate the relationship between financial performance and company value in the food and beverage sector